National Survey of Pharmacy Practice at MOH Hospitals in SAUDI Arabia 2016-2017: Pharmacy Computerized and Technology - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016-2017: Pharmacy Computerized and Technology. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into nine domains drove from American Society of Health-System Pharmacists (ASHP), Saudi Pharmaceutical Society (SPS) survey, and the international standard of Joint Commission of Hospital Accreditation. The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient’s education, Pharmacy inventory control and stock management, Pharmacy education and training. The 5-point Likert response scale system was used with closed and ended questions. An electronic questionnaire was distributed to the one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: Pharmacy Computerized and Technology. Results: The survey questionnaire was distributed to 185 of hospitals, the rate of reply was 105 (56.75%) hospitals. The majority of hospital pharmacies are not computerized and have no immediate plans to computerize 58 (55.2%) or Electronic Medical Record (EMR) 59 (56.2%). However, they had one or more component of the medical record (e.g., Medication administration record, CPOE, laboratory, radiology 42 (40.0%). The majority of hospital pharmacies had not Computerized Physician Order Entry (CPOE) at all, pharmacy services with average scores found 1.51 (30%) or Drug Alerting System through Computerized Physician Order Entry (CPOE) 1.35 (27%) only. Pharmacy technology in drug distribution network found in 17 (16.2%) hospitals only, and they used Automated transportation system 8 (7.6%) or centralized units dose (Cart filling machines, robotic arms) 5 (4.8%). Most of the hospital pharmacies did not have a plan for pharmacy automation or technology with average scores 1.66 (33.2%). Conclusion: Pharmacy computerization and technology seldom implemented at Ministry of Health hospitals. Targeting of strategic pharmacy informatics vision is required to prevent drug-related problems and avoid the unnecessary additional economic burden on healthcare system at Ministry of Health hospitals in Kingdom of Saudi Arabia.
Keywords: Pharmacy practice; Informatics; Automation; Technology; Ministry of health; Saudi arabia